Market Inefficiencies and Stock Anomalies: An Investigation of the Neglected and Reversal Effects - Jagadish, Ravi (Journal of Global Economy, Business and Finance, 2025)
In financial markets, the role of investor attention in shaping stock prices and returns has been recognized as a significant driver of market dynamics. This research investigates two relatively unknown market anomalies, the Neglected Stock Anomaly and the Reversal Anomaly, to provide insight on their implications for investors and market efficiency. The Neglected Stock Anomaly refers to undervalued stocks that receive little attention, perhaps leading to mispricing and prospects for above-average profits. The Reversal Anomaly, on the other hand, argues that stocks with poor short-term performance tend to have subsequent market declines, showing behavioural biases and opening up opportunities for contrarian tactics. This research adds to understanding market dynamics and providing insights for informed investment decision-making by investigating the connection between investor attention, market inefficiencies, and stock returns. Through empirical evidence and literature analysis, this study provides a comprehensive exploration of these anomalies, highlighting their connections and potential implications in various market conditions.